Penerapan Model Pembelajaran Sentra Terhadap Perkembangan Kemampuan Sosial Emosional Anak Usia Dini - Yeni Patriziana Regina Penuam; Rini Sansindi Taneo; Naomi Pitay; Nirlen Betti; Enderikanihu Fallo; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Early Childhood Education represents a critical period that significantly influences children's future development, particularly social-emotional development, which is essential for learning success and social interaction. This study aimed to measure the level of social-emotional development among children aged 4–6 years and to analyze the influence of the center-based learning model on their social-emotional development at PAUD Efrata Karisin, Kupang Regency, East Nusa Tenggara. The study employed a quantitative approach with an ex post facto design. The population and sample consisted of 20 children selected through total sampling. Data were collected using observation sheets, teacher interviews, and learning activity documentation. Data were analyzed using descriptive statistics and simple linear regression. The findings revealed that most children’s social-emotional development was in the low category (45%). Interview results further indicated that some children still experienced difficulties in taking turns, sharing, and resolving conflicts with peers. Hypothesis testing demonstrated a positive and significant effect of the center-based learning model on children’s social-emotional development, with a contribution of 6.4%. These findings suggest that the implementation of center-based learning, which aligns with the principles of meaningful, mindful, and joyful learning, contributes positively to children’s social-emotional development. However, greater consistency in implementing the learning model, along with active parental involvement, is needed to optimize developmental outcomes.